Evaluation of the establishment of a national task force - A systematic measure to manage critical drug shortages in hospitals - Joo Hanne Poulsen; Stine Raaby Jensen; Marianne Hald Clemmensen; Mikala Vasehus Holck; Nina Uldal; Trine Kart; Gitte Søndergaard Nielsen; Helle Armandi; og Lecia Møller Hansen (Elsevier, 2023)
Introduction: Drug shortages (DSs) have become a well-known challenge in health care, and serious patient safety consequences, such as medication errors and adverse patient outcomes are reported. To meet these challenges, a national task force was established to manage and minimize the impact of critical DSs' on hospitals in Denmark. Objective: To evaluate the establishment of the National Task Force for Critical Drug Shortages (NTF) in terms of quality, patient safety, and resources from different actor perspectives related to critical DS management in Danish hospitals. Methods: Five online focus group interviews were held with participants representing different actor perspectives, all of whom were involved in managing DSs. They represent actors from 1) the NTF; 2) hospital pharmacists not involved in the NTF but who manage DSs locally and/or regionally; 3) the procurement departments of hospital pharmacies; 4) pharmacy technicians performing clinical pharmacy services at a patient level, and 5) the procurement and supply unit at Amgros. Results: The thematic analysis revealed four major themes: 1) centralized management of critical DSs is predominantly considered to be positive, 2) collaboration and professional discussion across actors and actor levels, 3) mixed attitudes toward the current communication platforms and format, and 4) short supply of time. Conclusion: The NTF ensures a consistent and qualified management of critical DSs. The NTF ensures the evaluation of different patient safety aspects related to identification of a suitable alternative. Challenges with the communication platform and transparency of the process from the NTF toward hospital pharmacy were mentioned but overall, the NTF contributes to a successful use of resources in health care.